Intracerebral haemorrhage in young adults: the emerging importance of drug misuse. Issue 7245 (13th May 2000) - McEvoy, Andrew W; Kitchen, Neil D; Thomas, David G T
Abstract : In young people with haemorrhagic stroke, think of drug misuse and look for an underlying vascular cause